Essential Omega-3 (n-3PUFA) Nutritional Content of Ptilinopus melanosphila and Chalcophaps indicia Meat - Taslim D Nur; Sariffudin Fatmona; Sri Utami; Abd. Syukur Lumbessy (Jurnal Penelitian Pendidikan IPA, 2024)
Ptilinopus melanosphila and Chalcophaps indica, known as Puna birds among local people of the Sula Islands, North Maluku, Indonesia, while Treron aromaticus, known as Puna Giu, belong to the Columbidae family. These birds are frequently hunted for consumption due to the delectable taste of their meat. This study aims to examine the essential Omega-3 (n-3PUFA) nutritional content, utilizing these two avian species (Ptilinopus melanosphila and Chalcophaps indicia) as samples. Local perceptions consider these birds as identical, hence this study also provides insights into the disparities between the two species based on meat quality analysis. The analysis encompasses proximate analysis, fatty acids, and amino acids, conducted on 6 samples, each encompassing 3 breast meats. These samples were mixed and blended, followed by chemical analysis at the integrated laboratory of Universitas IPB Baranangsiang, with proximate analysis executed at PAU IPB. The results reveal that Ptilinopus melanosphila meat contains crucial nutrients for human consumption, specifically long-chain omega-3 unsaturated fatty acids (n-3PUFA), which are more abundant compared to Chalcophaps indica and several other meat products. The myriad of significant benefits offered by this avian species underscores the importance of recommending its preservation to parties engaged in ex-situ conservation efforts. Furthermore, it is advocated to stimulate the establishment of regional culinary businesses specializing in nutrient-rich Black-Naped Fruit Dove meat.